Optimalization of the Application of Act Number 22 of 2022 Concerning Companies in Overcoming Problems of Management of Corporate Institutions (Lapas) in Indonesia - Tasya Einakrisda Sheiba (Lex Prospicit, 2023)
The purpose of correctional systems is to improve the quality of personality and independence of inmates so that they are aware of their mistakes, improve themselves, and not repeat criminal acts, so that they can be accepted again by the community, can live normally as good citizens, obey the law, be responsible, and can play an active role in development. However, this correctional goal cannot be realized properly and optimally if the problems that exist in prisons are still not resolved properly. The type of research used in this paper is a type of empirical normative research. Collecting data using literature study methods and also interviews through the Forum Group Discussion (FGD), with the type of approach to legal systematics and Non-Judicial Case Study as well as data analysis in the form of qualitative research. Based on the research that the author did, can conclude that problems related to overcapacity, prison facilities and infrastructure, and human resources (prison officers) can be overcome by the establishment of Law Number 22 of 2022, but problems related to halinar cannot yet be resolved by Law No. 22 of 2022. The form of optimization strategy that can be done to overcome problems in prisons is to optimize the coaching activities provided to inmates, where prisoners become more active, not just as observers, apply restorative justice in prisons and one example is by providing a special room for mothers and children, as well as forming the National Correctional Agency (BAPASNAS).